PENENTUAN KADAR AIR, KADAR ABU, ZAT TERBANG DAN FIXED CARBON DALAM BATUBARA PT. TAMBANG BATUBARA BUKIT ASAM (PERSERO) TBK, TANJUNG ENIM - Renny Futeri; Gustiarini Rika Putri (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Coal is one of the fossil fuels which in general are sedimentary rocks that can be burned, formed from organic deposits, mainly are plant remnants and are formed through coalification processes. Coal has each characteristic that is different from each other depending on the level of the coal itself. The quality of coal is the nature of the physical and chemical properties of coal which affect its potential usefulness. Parameters used to determine coal quality include calculating water content, ash content, levels of flying and fixed carbon substances. From the test results of coal samples carried out the value of the water content can range from 6.26-12.42 %: ash content values obtained 3.06-7.87 %; the value of the flying substances obtained 36.94-44, 23% and the fixed carbon values obtained ranged from 41.96 to 48.86% with a standard water content of 1.29-21.66 %, ash content of 2.93-16.73 %; flying substance levels of 22.38-46.42 % and fixed carbon 37.8-98% . From the analysis data, it can be concluded that the water content, ash content, and flying substances contained in the sample have met the standards of the ASTM (American Society for Testing and Materials) used by PT. Coal Mine Bukit Asam (Persero) Tbk, Tanjung Enim.